2017
DOI: 10.1371/journal.pone.0173519
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and association of refractive anisometropia with near work habits among young schoolchildren: The evidence from a population-based study

Abstract: BackgroundLifestyle behaviour may play a role in refractive error among children, but the association between near work habits and refractive anisometropia remains unclear.MethodsWe estimated the prevalence of refractive anisometropia and examined its association with near work activities among 23,114 children in the Myopia Investigation Study in Taipei who were grade 2 elementary school students at baseline in 2013 and 2014. Baseline data on demographics, medical history, parental history and near work habits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…In our study, we found that a distance from near work of less than 30 cm and not taking breaks after 30 minutes of continuous reading were associated with increased myopia. This finding was consistent with those of studies from China 25,47 and Australia. 32 We also found that either parents' wearing of spectacles was associated with student myopia.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found that a distance from near work of less than 30 cm and not taking breaks after 30 minutes of continuous reading were associated with increased myopia. This finding was consistent with those of studies from China 25,47 and Australia. 32 We also found that either parents' wearing of spectacles was associated with student myopia.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the initial astigmatism power was identified as an important predictive variable for changes in refractive error. In fact, the presence of an astigmatism greater than or equal to −1.5 D, due to modifications in the corneal curvature, was more significantly associated with increased changes in refractive error over the follow-up years [103].…”
Section: Treatmentsmentioning
confidence: 99%
“…According to the Ojai longitudinal study, the prevalence of anisometropia among 5–14-year-old children ranged between 0.9% and 2.4% 4 . In a more recent large population-based study, the prevalence of anisometropia among school-aged children was 5.3% 5 . The physician should be aware that the degree of anisomyopia may increase with the progression of myopia over time .…”
Section: Introductionmentioning
confidence: 95%